Balāgah al-Jasad al-Furjūwī baina al-Ta’bīr al-Ĥarakī wa al-Kalimah al-Manṭūqah Masraḥiyyah “Kharīf” Numūżajā - El Haouari, Yassine (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to analyze body rhetoric between motor expressions and spoken words in the play "Kharif" as a model for the work of director Asmaa Houri. This qualitative research has a case study type of research on literary appreciation in drama performances in Morocco. The research data is in body rhetoric played by several drama actors. Data collection techniques use in-depth observation and documentation. The data analysis uses data reduction, data presentation, and conclusion. The research results show that the body is important in constructing a drama performance. Rather, the motor elements contribute to the production of a diverse group of connotations. Several topics that shape the picture of contemporary drama in Maraco include women's movements and the duality of body and soul, men's and the duality of presence and absence, body language related to eye movements, and silence and the body in choreography.